2021
DOI: 10.30564/jgr.v4i2.3100
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Seasonal Variation in the Distribution and Concentration of Heavy Metals Using Water Quality Index and Geographic Information System Based Applications

Abstract: Incessant monitoring of water is essential in terms of heavy metals and toxic substances as it provides detailed information on aquatic resources. Majority of lagoons receive freshwater from their catchment areas containing industrial and domestic waste. The paper analysed seasonal variations in the distribution and concentrations of Lead (Pb), Copper (Cu), Cadmium (Cd), and Manganese (Mn) in the Fosu lagoon in Ghana to ascertain the quality of the lagoon. Water was sampled from eighteen (18) different points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The results from the water quality analysis of the Chemu lagoon showed that turbidity, temperature, sulphate, phosphates, faecal coliforms, biological oxygen demand, zinc, manganese, lead, and cadmium exceeds the USEPA's permissible limits. This finding is in line with Adu-Boahen and Boateng [23] studies on the Fosu lagoon in Ghana that revealed higher concentrations of like parameters. Similar results were recorded by Biney [15] in the Chemu Lagoon.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results from the water quality analysis of the Chemu lagoon showed that turbidity, temperature, sulphate, phosphates, faecal coliforms, biological oxygen demand, zinc, manganese, lead, and cadmium exceeds the USEPA's permissible limits. This finding is in line with Adu-Boahen and Boateng [23] studies on the Fosu lagoon in Ghana that revealed higher concentrations of like parameters. Similar results were recorded by Biney [15] in the Chemu Lagoon.…”
Section: Discussionsupporting
confidence: 91%
“…Water samples were collected from the lagoon to assess the level of contamination of the Chemu Lagoon. Five sampling points were determined after [23]. The samples were collected and stored in a high-density polyethene bottle.…”
Section: Sampling Data Collection and Analysismentioning
confidence: 99%
“…Remote sensing (RS), gathering information about an object or phenomenon from a distance, typically using aircraft or satellite-based sensors, and geographical information systems (GIS) have emerged as indispensable tools in monitoring and strategically managing metal/metalloid stress in agriculture. By offering detailed insights into contamination levels and their spatial distribution, RS and GIS enhance the development, implementation, and evaluation of targeted mitigation strategies [64,65].…”
Section: Advanced Tools For Monitoring and Assessing Soil Metal/metal...mentioning
confidence: 99%
“…RS technology facilitates the early detection of physiological alterations in crops attributable to metal/metalloid exposure, thereby allowing for targeted mitigation measures [64]. Concurrently, GIS's spatial analytical capabilities are pivotal in identifying contamination hotspots and assessing the spread of metal/metalloids within agricultural landscapes, which is crucial for formulating and monitoring effective mitigation strategies [65].…”
Section: Applications and Advantagesmentioning
confidence: 99%
“…The earlier scholars have focused on beach sedimentation, particle size analysis of beach sediment, coastline analysis and erosion rate, shoreline dynamics of the coast, and development of coastal beach stabilisation. Others (Adu-Boahen & Boateng, 2021;Okyere, Adu-Boahen et al, 2023;Adu-Boahen et al, 2023) also studied the physicochemical analysis or composition of lagoons and ways of reducing storm impacts on coastal lands and making coastal environments safe for habitation. Even though the above studies were geared towards creating awareness of these phenomena in the coastal environment aimed at protecting lives and properties, much effort has not been made to study specific coastal landforms such as the barrier beach.…”
Section: Introductionmentioning
confidence: 99%